Expression of Programmed Death Ligand 1 (PD-L1) in Posttreatment Primary Inflammatory Breast Cancers and Clinical Implications. Issue 3 (7th February 2018) - He, Jing; Huo, Lei; Ma, Junsheng; Zhao, Jun; Bassett, Roland L; Sun, Xiaoping; Ueno, Naoto T; Lim, Bora; Gong, Yun
Abstract: Objectives: Inflammatory breast carcinoma (IBC) is rare but is the most lethal type of breast cancer. Programmed death ligand 1 (PD-L1) expression in IBCs has been understudied. Methods: In this study, tissue microarrays of 68 IBCs were immunostained with a PD-L1 antibody using an antibody clone (28-8) and detection system approved by the US Food and Drug Administration for selecting patients with non–small cell lung cancer and melanoma for anti–PD-L1 therapy. Results: Positive PD-L1 expression was found in 25 (36.8%) of 68 samples but was not significantly associated with the clinicopathologic variables examined. Univariate analysis of overall survival (OS) revealed that worse OS was significantly associated with positive PD-L1, negative estrogen receptor, and triple-negative status. The 5-year OS rate was 36.4% for patients with PD-L1–positive IBC and 47.3% for those with PD-L1–negative IBC. In multivariate analyses, PD-L1 status remained a statistically independent predictor of OS. Conclusions: These findings indicate that PD-L1 inhibitors could potentially improve the clinical outcome of patients with PD-L1–positive IBC.